What are the affordances of the digital music space in alternative education? A reflection on an exploratory music outreach project in rural Australia. (August 2021) - English, Helen J; Lumb, Matt; Davidson, Jane W
In Australia, access to music education is inequitable due to the challenges of distance, different state education systems and a lack of resources in schools. As a means to address this social justice issue, we explore here the viability and effects of a digitally based music outreach programme undertaken in collaboration with Hands on Learning (HOL), an alternative education provider. The programme was delivered over 6 weeks using GarageBand to children in a small rural town who were experiencing difficulties in upper primary and lower secondary school years. A qualitative approach was taken, holding focus groups, observing sessions and accessing HOL daily notes. The programme had a significant impact on the teachers and children involved, showing promise for a larger scale project in the future.